Atenea Exams, an IMS LTI Application to Solve Scalability Problems: A Study Case - Marc Alier; María José Casany; Ariadna Llorens; Jesús Alcober; Joana d’Arc Prat (Applied Sciences, 2020)
In 2004, the Universitat Politècnica de Catalunya decided to change one of its critical and strategic information services: the online teaching support platform. An Open Source software, Moodle, was adopted and the previous proprietary software was abandoned. In 2020, the home confinement of the population due to the pandemic caused by COVID-19 has been a stress test for the entire university community, and very specifically by those responsible for providing the support of the online teaching support platform. The increase in activity and the prospect of the generalization of online assessment raised the concerns of possible scalability issues with the quiz functionality during the examination period. The solution applied involved using Moodle’s IMS LTI interoperability features to deploy a high-performance version of the Moodle Quizz Module As A Service (SaaS), to plug-and-play within the university’s LMS without drawing on its internal resources. This solution combined with a systems strategy, private cloud operations, internal communication and teacher training, solved this problem and successfully complete the assessment of the university course in a situation of confinement.